Group Fanaticism in the Perspective of Hadith: Its Implications for Islamic Education Based on Sunan Abu Dawud 5119 - Iswanto Iswanto; Imam Asyrofi; Githo Githo (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
Group fanaticism is an attitude of excessively defending a group even when it is in the wrong or unjust position. In contemporary society, this phenomenon has intensified and frequently triggers horizontal conflicts, social polarization, and hinders the realization of moderate and harmonious religious life. The hadith in Sunan Abu Dawud number 5119 serves as a normative reference that explicitly prohibits blind fanaticism, making it highly relevant to be examined from the perspective of Islamic education. This study aims to analyze the authenticity of the hadith and explore its educational implications. The research employs a qualitative approach through sanad and matn analysis, complemented by a conceptual pedagogical framework. The novelty of this study lies in integrating classical hadith criticism with an analysis of its educational implications in contemporary Islamic education. The findings indicate that the sanad is classified as sahih li ghayrih and the matn as sahih li dhatihi, thus categorized as maqbul ma‘mulun bihi and suitable as a normative foundation. The hadith embodies educational values such as anti-fanaticism, religious moderation (wasathiyah), tolerance, critical thinking, and inclusivity. Its implications highlight that this hadith functions not only as a theological norm but also as a foundational basis for curriculum development, instructional strategies, and character education aimed at fostering moderate, critical, and socially harmonious learners in multicultural societies.